Curcumin and nano‐curcumin applications in psychiatric disorders - Mohammadzadeh, R.; Fathi, M.; Pourseif, M. M.; Omidi, Y.; Farhang, S.; Barzegar Jalali, M.; Valizadeh, H.; Nakhlband, A.; Adibkia, K. (Phytotherapy research, 2024)
Psychiatric disorders cause long‐lasting disabilities across different age groups. While various medications are available for mental disorders, some patients do not fully benefit from them or experience treatment resistance. The pathogenesis of psychiatric disorders involves multiple mechanisms, including an increase in the inflammatory response. Targeting inflammatory mechanisms has shown promise as a therapeutic approach for these disorders. Curcumin, known for its anti‐inflammatory properties and potential neuroprotective effects, has been the subject of studies investigating its potential as a treatment option for psychiatric disorders. This review comprehensively examines the potential therapeutic role of curcumin and its nanoformulations in psychiatric conditions, including major depressive disorder (MDD), bipolar disorder, schizophrenia, and anxiety disorders. There is lack of robust clinical trials across all the studied psychiatric disorders, particularly bipolar disorder and schizophrenia. More studies have focused on MDD. Studies on depression indicate that curcumin may be effective as an antidepressant agent, either alone or as an adjunct therapy. However, inconsistencies exist among study findings, highlighting the need for further research with improved blinding, optimized dosages, and treatment durations. Limited evidence supports the use of curcumin for bipolar disorder, making its therapeutic application challenging. Well‐designed clinical trials are warranted to explore its potential therapeutic benefits. Exploring various formulations and delivery strategies, such as utilizing liposomes and nanoparticles, presents intriguing avenues for future research. More extensive clinical trials are needed to assess the efficacy of curcumin as a standalone or adjunctive treatment for psychiatric disorders, focusing on optimal dosages, formulations, and treatment durations. Curcumin and nano‐curcumin applications for psychiatric disorders.